2018
DOI: 10.1039/c8cs00236c
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of defects and dopants in 2D layered transition metal dichalcogenides

Abstract: Layered transition metal dichalcogenides (TMDs) offer monolayer 2D systems with diverse properties that extend beyond what graphene alone can achieve. The properties of TMDs are heavily influenced by the atomic structure and in particular imperfects in the crystallinity in the form of vacancy defects, grain boundaries, cracks, impurity dopants, ripples and edge terminations. This review will cover the current knowledge of the detailed structural forms of some of the most intensively studied 2D TMDs, such as Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
176
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(186 citation statements)
references
References 172 publications
2
176
0
Order By: Relevance
“…Defects in these types of systems can break symmetries, scatter excitations, modify energy landscapes, and create quantum confinement. They often dictate material properties by controlling the creation, transport, and interconversion of excitations involved in electronic, optoelectronic, magnetic, thermal, or superconducting response, [195][196][197][198][199] and therefore, must be controlled to prevent degradation of material properties. Defects can be used extensively to control and tailor the properties of 2D materials for a variety of applications and also provides a platform to elucidate fundamental physical phenomena in 2D materials.…”
Section: Defectsmentioning
confidence: 99%
“…Defects in these types of systems can break symmetries, scatter excitations, modify energy landscapes, and create quantum confinement. They often dictate material properties by controlling the creation, transport, and interconversion of excitations involved in electronic, optoelectronic, magnetic, thermal, or superconducting response, [195][196][197][198][199] and therefore, must be controlled to prevent degradation of material properties. Defects can be used extensively to control and tailor the properties of 2D materials for a variety of applications and also provides a platform to elucidate fundamental physical phenomena in 2D materials.…”
Section: Defectsmentioning
confidence: 99%
“…[53] As one of the most investigated 2D nanomaterials, few layered MoS 2 nanosheets have been extensively doped with ions and atoms to regulate their structures and properties (Figure 3a). [53] As one of the most investigated 2D nanomaterials, few layered MoS 2 nanosheets have been extensively doped with ions and atoms to regulate their structures and properties (Figure 3a).…”
Section: Element Doping With Ions and Atomsmentioning
confidence: 99%
“…As another anion vacancy, sulfur vacancies can be produced by chemically exfoliating layered transition metal chalcogenides such as MoS 2 to single molecular layers. [66] Recently, researchers have paid high attention to the sulfur vacancies in the formation of SACs; atoms can anchor on these vacancies with high affinities, and thus the sulfur vacancy defects can be used to stabilize metal atoms. Liu et al reported chemically exfoliated bulk MoS 2 through Li intercalation to form MoS 2 molecular layers with rich sulfur vacancies on the basal plane.…”
Section: Anion Vacanciesmentioning
confidence: 99%